2022
DOI: 10.1177/10567895221132868
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-mechanical coupling characteristics and damage constitutive model of low-permeability granite under triaxial compression

Abstract: To investigate the effect of hydro-mechanical coupling characteristic in low-permeability hard rocks during the excavation of groundwater-sealed energy cavern and hydraulic engineering tunnels or chambers, triaxial compression tests were conducted on engineering granite under different confining and seepage pressures. The mechanical properties, such as the strength and deformation parameters, of granite under hydro-mechanical coupling condition were studied. The permeability of the granite under different stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…According to Figure 9, it can be found that the limitation of the permeability of rock samples by the pressure was quite critical. Zheng et al [38] suggested that this is because the confining pressure acts to consolidate the pore and fissure pressures within the rock sample. It should be noted that the four parts, I, II, III, and IV, divided in Figure 10 correspond to the crack closure stage (I), linear elasticity stage (II), stable crack expansion stage (III), and unstable crack expansion stage (IV), respectively.…”
Section: Analysis Of Seepage Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Figure 9, it can be found that the limitation of the permeability of rock samples by the pressure was quite critical. Zheng et al [38] suggested that this is because the confining pressure acts to consolidate the pore and fissure pressures within the rock sample. It should be noted that the four parts, I, II, III, and IV, divided in Figure 10 correspond to the crack closure stage (I), linear elasticity stage (II), stable crack expansion stage (III), and unstable crack expansion stage (IV), respectively.…”
Section: Analysis Of Seepage Evolutionmentioning
confidence: 99%
“…According to Figure 9, it can be found that the limitation of the permeability of rock samples by the pressure was quite critical. Zheng et al [38] suggested that this is because the confining pressure acts to consolidate the pore and fissure pressures within the rock sample.…”
Section: Analysis Of Seepage Evolutionmentioning
confidence: 99%
“…Based on these strength criteria, the corresponding perfect elastoplastic model is established, which can reflect the linear elastic deformation characteristics and strength characteristics of rock but cannot describe the pre-peak plastic hardening behaviour of rock. Some scholars proposed models to reflect the pre-peak hardening nonlinear behaviour of rock based on elastoplastic theory (Feng and Liu, 1996; Makhnenko and Labuz, 2015; Siddiquee and Hamdi, 2019; Wang et al., 2018, 2020; Xu, 2021; Zheng et al., 2022d). To characterize the post-peak softening of rock, some scholars have systematically studied mechanical behaviour of rock using macroscopic and microscopic mechanics and established some elastoplastic damage constitutive models (Bikong et al., 2015; Feng et al., 2004; Feng and Yu, 2010; Ju, 1989, 1990; Kim and Lee, 2011; Qu, 2021; Shao and Rudnicki, 2000; Wang and Ma, 2022; Zhang, 2022; Zhao et al., 2018; Zheng et al., 2022c).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, researchers connected statistical theory, damage theory and continuum mechanics (Jiang et al., 2022; Krajcinovic and Silva, 1982; Liu and Zhang, 2015; Song et al., 2022; Weibull, 1951; Xie and Gao, 2000), which promoted the development of rock constitutive models. Scholars have used functions such as normal distribution, log-normal distribution and Weibull distribution to characterize microunit features (Chen et al., 2018, 2021; Ji et al., 2019; Zheng et al., 2022d). In addition, with the development of modern information theory, the use of entropy to fit the microscopic properties of rocks has also achieved good results (Deng and Gu, 2011; Deng and Pandey, 2009).…”
Section: Introductionmentioning
confidence: 99%